Novel viruses determined using fecal virome analysis in the feces of foals with diarrea - Vega, Celina Guadalupe (2016)
This study aims to expand the knowledge of viral species present in feces of foals suffering diarrhea using Next Generation Sequencing. This will be useful to further explore the role of new infectious agents in this illness in foals.